Digital dance scholarship: Biomechanics and culturally situated dance analysis. - Varela, Miguel Escobar; Hernández-Barraza, Luis (Digital Scholarship in the Humanities, 2020)
This article explores the intersection of biomechanics and culturally situated dance scholarship. We focus on 'Sendratari Ramayana', a 50-year-old dance form heavily influenced by classical Javanese dance traditions dating back to the 19th century. We used a full-body plug-in gait model to record differences in character typology—a key concern of Javanese dance scholarship. The results are presented through online visualizations and analyzed quantitatively. This approach outlines a digital stylometry of movement that contributes to the long tradition of formalist analysis of Javanese dance.